Cerebrospinal Fluid Amyloid β1-42, Tau, and Alpha-Synuclein Predict the Heterogeneous Progression of Cognitive Dysfunction in Parkinson’s Disease - Kang, Ju-Hee (Journal of movement disorders, 2016)
Parkinson's disease (PD) is a neurodegenerative disease with heterogeneous pathological and clinical features. Cognitive dysfunction, a frequent non-motor complication, is a risk factor for poor prognosis and shows inter-individual variation in its progression. Of the clinical studies performed to identify biomarkers of PD progression, the Parkinson's Progression Markers Initiative (PPMI) study is the largest study that enrolled drug-naïve and very early stage PD patients. The baseline characteristics of the PPMI cohort were recently published. The diagnostic utility of cerebrospinal fluid (CSF) biomarkers, including alpha-synuclein (α-syn), total tau, phosphorylated tau at Thr181, and amyloid β1-42, was not satisfactory. However, the baseline data on CSF biomarkers in the PPMI study suggested that the measurement of the CSF biomarkers enables the prediction of future cognitive decline in PD patients, which was consistent with previous studies. To prove the hypothesis that the interaction between Alzheimer's pathology and α-syn pathology is important to the progression of cognitive dysfunction in PD, longitudinal observational studies must be followed. In this review, the neuropathological nature of heterogeneous cognitive decline in PD is briefly discussed, followed by a summarized interpretation of baseline CSF biomarkers derived from the data in the PPMI study. The combination of clinical, biochemical, genetic and imaging biomarkers of PD constitutes a feasible strategy to predict the heterogeneous progression of PD.